Latitudinal and temporal distributions of diatom populations in the pelagic waters of the Subantarctic and Polar Frontal zones of the Southern Ocean and their role in the biological pump - Rigual-Hernandez, AS; Trull, TW; Bray, SG; Cortina, A; Armand, LK (2015)
The Subantarctic and Polar Frontal zones (SAZ and PFZ) represent a large portion of the total area of the Southern Ocean and serve as a strong sink for atmospheric CO 2 . These regions are central to hypotheses linking particle fluxes and climate change, yet multi-year records of modern flux and the organisms that control it are, for obvious reasons, rare. In this study, we examine two sediment trap records of the flux of diatoms and bulk components collected by two bottom-tethered sediment traps deployed at mesopelagic depths (~ 1 km) in the SAZ (2-year record; July 1999–October 2001) and in the PFZ (6-year record; September 1997–February 1998, July 1999–August 2000, November 2002–October 2004 and December 2005–October 2007) along the 140° E meridian. These traps provide a direct measure of transfer below winter mixed layer depths, i.e. at depths where effective sequestration from the atmosphere occurs, in contrast to study of processes in the surface ocean. Total mass fluxes were about twofold higher in the PFZ (24 ± 13 g m −2 yr −1 ) than in the SAZ (14 ± 2 g m −2 yr −1 ). Bulk chemical composition of the particle fluxes mirrored the composition of the distinct plankton communities of the surface layer, being dominated by carbonate in the SAZ and by biogenic silica in the PFZ. Particulate organic carbon (POC) export was similar for the annual average at both sites (1.0 ± 0.1 and 0.8 ± 0.4 g m −2 yr −1 for the PFZ and SAZ, respectively), indicating that the particles in the SAZ were relatively POC rich. Seasonality in the particle export was more pronounced in the PFZ. Peak fluxes occurred during summer in the PFZ and during spring in the SAZ. The strong summer pulses in the PFZ are responsible for a large fraction of the variability in carbon sequestration from the atmosphere in this region. The latitudinal variation of the total diatom flux was found to be in line with the biogenic silica export with an annual flux of 31 ± 5.5 × 10 8 valves m −2 yr −1 at the PFZ compared to 0.5 ± 0.4 × 10 8 m −2 yr −1 at the ...